Política de evaluación del desempeño organizacional, primer nivel de atención de Costa Rica: resultados preliminares (Repertorio Científico, 2023)
The objective of this paper is to describe the design of the organizational performance evaluation policy (POLEDO) at the first level of care of the Costa Rican Social Security Fund (CCSS) during the years 2018-2022. Methodology under the constructivist paradigm, with a qualitative approach with the use of hermeneutic, ethnographic, and grounded theory methods that allow analyzing the interrelation between scientific knowledge and the design of institutional actions in the evaluation of organizational performance in the provision of services health services at the first level of care, as effective responses that contribute to the quality of life of society. In general, the first results show the conglomerate of mechanisms or instruments that converge in the design of the analysis policy, as well as the number of actors that intervene and the work networks that are interwoven to achieve a response in the provision of services. health services at the first level of care. This shows the complexity of the negotiation processes between individual and collective interests, with a mix of managerial, technical, legal, and operational organization.